الصور الكنائية في مختارات كتاب الأذكياء لأبي الفرج ابن الجوزي / Allegorical Images in the Book "Mukhtarat Kitab Al-Adzkiya" by Abi Al-Faraj Ibn Al-Jauzi - Rofidah, Ni’ma; Munjiah, Maâ€™rifatul (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
كانت للإمام أبو الفرج بن الجوزي مؤلفات كثيرة في عدة فنون. ومن أشهر كتبه كتاب "أخبار الأذكياء" وهو كتاب رائع يذكر فيه أخبار الأذكياء من الأنبياء والعلماء والأمراء والقضاة وغيرهم. فإنعام النظر في تراث ابن الجوزي هذا مما يعطي لنا قطرة النماذج من كلام العلماء ومن صلح من الأذكياء بلاغة و فصاحة عناية على الكناية التي هي أبلغ أنواع علم البيان. لذلك، اتخذت الباحثة مختارات من كتاب "أخبار الأذكياء" كمصدر لهذا البحث. فيهدف هذا البحث إلى وصف أشكال الكناية في النص باعتبار وسائطها. استخدمت الباحثة في هذا البحث المنهج الوصفي الكيفي، فجمعت البيانات بطريقة القراءة وبحث المعاني ثم تصنيف النصوص التي فيها كنايات من حيث الوسائط والسياق، ويجري في التحليل من إيجاد أركان الكناية إلى الاستخراج بطريقة الاستقراء والاستنتاج. فتشير نتيجة البحث إلى تشكيل أربعة أنواع من الكناية من حيث الوسائط والسياق وهي التعريض والتلويح والرمز والإيماء. Abstract Imam Abu Al-Faraj Ibn Al-Jawzi has several works in various arts. The book "Akhbar al-Adzkiya" is one of his most recognized works. It is a lovely and magnificent book in which he discusses the news of wise individuals such as prophets, intellectuals, judges, and others. A detailed examination of this inheritance reveals a smattering of examples from the words of scholars and spiritual individuals from among the brightest who care about Kinayah’s style with eloquence and eloquence. In terms of euphemism, the researcher used the "Mukhtarat Kitab al-Adzkiya," which is a condensed version of the book "Akhbar al-Adzkiya," as the subject of this research, acknowledging the media and context. The researcher used a qualitative descriptive technique to collect data, so she read and repeated the confined news to understand the confusing meanings, then did a taxonomy analysis based on the extrapolation forms of metonymy. Including the findings of the study, four forms of metonymy are generated when the medium and context are taken into account. Exposed (al-Ta’ridl), waving (al-Talwih), symbolizing (al-Ramz), and nodding (al-imaa’/isyarat) are all examples. Keywords: Abu al-Faraj Ibn al-Jauzi; Akhbar al-Adzkiya; Kinayah